Hubungan Pengetahuan Ibu Yang Memiliki Balita Tentang Gerakan 1000 Hari Pertama Kehidupan (HPK) Dengan Kejadian Stunting Pada Balita Di Posyandu Pakuhaji Kabupaten Tangerang : (The Relationship Between Mothers' Knowledge of Toddlers About the First 1000 Days of Life (HPK) Movement and Stunting Incidents in Toddlers at Posyandu Pakuhaji, Tangerang Regency - Husnul Khotimah, Siti Hayat; Mariyani (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Stunting is one of the most common child health problems in the world. High knowledge about 1000 HPK will provide insight in applying the role of women's lives starting from preparing for pregnancy, becoming pregnant, and then becoming a mother will also provide knowledge to the child to be born.  Methods: Quantitative analysis with a cross-sectional approach. The sample consisted of 182 mothers with toddlers aged 25-59 months who were in the Posyandu, Pakuhaji District, Tangerang Regency, using a proportional stratified random sampling technique. Bivariate analysis using the Chi-Square test.  Results: The results of the univariate study showed that mothers' knowledge was mostly good (74,7%), and the incidence of stunting in toddlers was mostly normal (84,6%). Bivariate research results with p-value = 0,000.  Discussion: There is a relationship between a mother's knowledge about the First 1000 Days of Life (HPK) movement and the incidence of stunting in toddlers.